ST Segment “Hump” during Exercise Testing and the Risk of Sudden Cardiac Death in Patients with Hypertrophic Cardiomyopathy - Michaelides, Andreas P. (Ann Noninvasive Electrocardiol, 2009)
Background: The appearance of a discrete upward deflection of the ST segment termed “the ST hump sign” (STHS) during exercise testing has been associated with resting hypertension and exaggerated blood pressure response to exercise. Objective: We investigated the prevalence and clinical significance of this sign in a population of patients with hypertrophic cardiomyopathy. Methods: Eighty‐one patients with hypertrophic cardiomyopathy (HCM) who underwent cardiopulmonary exercise testing were followed in a retrospective cohort study for a mean period of 5.3 years. Results: The appearance of the STHS at the peak of exercise testing was observed in 42 patients (52%), particularly in the inferior and the lateral leads. Patients with the STHS had higher fractional shortening and maximum left ventricular wall thickness and exhibited more frequently outflow tract gradient >30 mmHg at rest. Furthermore, the presence of STHS was a strong independent predictor of the risk of sudden cardiac death (SCD), as the latter occurred in eight of the patients with this sign (8/42, 19%) and in none of the patients without it (0/39, 0%) (P < 0.001). Conclusion: The appearance of a “hump” at the ST segment during exercise testing appears to be a risk factor for SCD in patients with HCM. However, further studies are necessary to validate this finding in larger populations and to elucidate the mechanism of the appearance of the “hump.”